Pengaturan Tanggungjawab Negara Terhadap Penanganan Fakir Miskin Dalam Undang-Undang Nomor 13 Tahun 2011 Dikaitkan Dengan Hak Asasi Manusia - Irwansyah Eka Putra; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Handling the Poor is the responsibility of the state in guaranteeing human rights in an effort to improve social welfare in Indonesia. This study aims to examine the problem of handling the poor who are made by the state in this case the government based on Law No. 13 of 2011 concerning Management of the Poor.The research method used in this thesis is normative legal research or also known as library research, namely research conducted with a normative juridical approach through the study of literature as secondary data. This study uses qualitative data analysis and produces descriptive data.The results of the study, first concluded that the regulation of state responsibility for the handling of the Poor in Law number 13 of 2011 does not guarantee human rights, because there has not been a fair and equitable social welfare condition. Second, the ideal form of regulation regarding the handling of the poor in Indonesia with the problem of poor people is dynamic and complex. Requires policies and strategies that are flexible, sustainable and based on human rights, so that the achievement of Social Welfare for the Poor.The author's suggestion, is the first need to be made changes to the Law 13 of 2011 concerning the Management of the Poor on the basis of social welfare development, social change, and rights-based. And it is hoped that going forward in the strategy of handling the Poor, it is not only focused on help, but must be accompanied by empowerment. The availability of an integrated database to be the basis for Handling the Poor so that it is right on target. Second, Requires a gradual and planned handling and evaluation and overall oversight because it is not easy to complete in a short time. Arrangements and strategies in handling the Poor by the State by following changes in the situation and conditions that develop in society can be seen from the symptoms and social change.Keywords: Poor - Human Rights - State